(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The decade of the 1960s in the United States is commonly viewed and taught as a series of traditional dichotomies, white vs. black, male vs. female, liberal vs. conservative, communist vs. anti-communist. Recent American scholarship on this period reveals a much more complex interplay of forces and movements. President John F. Kennedy’s government was attacked for its policy toward the Soviet Union and communism in general, from both the right and the left. Political conservatism witnessed a revival at the expense of the then-dominant liberal culture. Martin Luther King promoted an economic and social agenda that went well beyond the vision of “I Have a Dream”. Together, these forces enacted a second American “Civil War”, which was a much more complex struggle than is commonly understood or taught. The History educator dealing with USA in the FET history curriculum is exposed to some interesting information to be utilised and debated in classrooms.